Tracking the microplastic accumulation from past to present in the freshwater ecosystems: A case study in Susurluk Basin, Turkey - Almas, Fatma Feisal; Bezirci, Gizem; Cagan, Ali Serhan; Gokdag, Kerem; Cirak, Tamer; Kankilic, Gokben Basaran; Pacal, Elif; Tavsanoglu, Ulku Nihan (Elsevier BV, 2022)
Microplastic pollution in aquatic ecosystems has become a global issue in recent years due to its presence everywhere around the world. Although several studies have explored the impact of the accumulation of those small particles in marine environments, comparisons of freshwater systems with marine environments are scarce. In the current study, due to the lack of long-term data on microplastic pollution, we used paleolimnological approaches to acquire the missing information regarding this hot topic. Two short cores were taken from Bursa province in Turkey, which is the center of industrial and agricultural production with many different sectors such as textile and manufacturing. The first core sample was taken from a relatively pristine environment, Lake Uluabat, and the second one was taken from a delta area where all the discharge coming from the basin flowed through to the Marmara Sea. The sediment core from the lake was dated back to the 1960's and the majority of the sample was dominated by fibers. Despite there being no uniform distribution pattern, the number of the microplastics showed decreasing trend after the lake became a Ramsar site. Due to the continuous mixing in the sampling area, there were obstacles via the dating of the Delta core. Nevertheless, the data showed that a high number and variety of microplastics have accumulated over the last decade in the province. This can be interpreted as microplastic pollution reaching the sea directly from the basin. These findings revealed that a plastic chronostratigraphy would give important temporal data regarding the microplastic accumulation in aquatic ecosystems.
Keywords: Lake Uluabat; Turkey; Microplastics; Microplastics; Emergent contaminant; Paleolimnology; Ramsar site; Lake uluabat; Koca?ay delta; Lakes; Emergent Contaminant; Kocaçay Delta; Paleolimnology; Ramsar Site; Plastics; Ecosystem; Water Pollutants, Chemical; Environmental Monitoring; 15. Life on land; 6. Clean water; 13. Climate action; 14. Life underwater